Attitudes Toward Organ Donation for Persons Who Have a Substance Use Disorder Relative to Other Health Conditions - Grubb, Caitlyn J.; Bergeria, Cecilia L.; Huhn, Andrew S.; Dunn, Kelly E. (Frontiers in Psychiatry, 2021)
Background: Increases in opioid-related overdose and death have led to increases in the number of organs available for donation and transplant, however persons who have a substance use disorder (SUD) may be disadvantaged relative to other health conditions with regard to receiving an organ for transplant. Objective: This study aimed to evaluate perceptions regarding acceptability and priority for organ donation versus a control condition (resuscitation) for hypothetical persons with nine target health conditions including a substance use disorder, among persons recruited as part of an online survey. Methods: Respondents (N=285; male=172, female=113) recruited from Amazon Mechanical Turk rated acceptability and priority that hypothetical persons representing nine target health conditions expected to influence transplant success (including a SUD) receive an organ transplant and resuscitation via a survey hosted by Qualtrics. Primary outcomes of stigma ratings and priority ranking of persons as a function of the hypothetical target health condition were analyzed using Repeated Measures Analyses of Variance and Bonferroni-corrected t-tests. Demographic information was presented descriptively for all respondents. Results: Ratings for acceptability and priority for persons who had a SUD were generally lower than ratings for other conditions for both organ for transplant and resuscitation, though respondents reported less stigma towards resuscitation, F(8) = 22.35, p < .001 overall. Respondents were least supportive of persons who smoked cigarettes receiving an organ, p’s < .001. Priority rankings favored persons who were young or had a history of heart disease. Multivariable models determined that target health condition, F (8) = 33.64, p < .001, was a better and more consistent predictor of response than demographic variables that were examined. Conclusions: Data suggest that general perception of acceptability and priority ranking for receipt of life-saving interventions was lower for persons who have a SUD relative to other clinically-relevant health conditions. Research to examine this effect among persons working in the donation system are warranted and efforts to reduce stigma towards persons who have a SUD should be continued.